The Influence of Leadership Style, Organizational Support, and Incentives on PT Employee Work Productivity. Sai Apparel Industries - Ulya, Chikmatul Ulya; Sijabat, Rauly; Kurniawan, Bayu (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to determine the factors of leadership style, organizational support, and incentives on the work productivity of PT employees. Sai Apparel Industries. This research used questionnaires that were distributed directly as data collection material. The sample in this study was 370 respondents, who were analyzed using the SPSS 26 application. The research objects as independent variable factors were leadership style, organizational support and incentives. Meanwhile, the dependent variable is employee work productivity. Hypothesis testing was carried out using a multiple linear regression analysis model. The research results show that the partial test or t test for each variable has a positive and significant effect on employee work productivity. This can be seen from the leadership style variable of 6.791 with a significance of 0.000, and the organizational support variable of 3.065 with a significance of 0.002, while the incentive variable is 6.153 with a significance of 0.000. In the F test or simultaneous variables, leadership style, organizational support and incentives have a significant effect of 91.780 on the work productivity of PT employees. Sai Apparel Industries.